Peran Orang Tua Sebagai Pendidik Anak Dalam Keluarga - Adrian, Adrian; Syaifuddin, Muhammad Irfan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2017)
Abstract This article discusses the role of parents as child educators in the household. Many Muslim scholars quoted quran verses and hadith as the basis for the importance of children's education in the family. The family is the smallest instrument in the community and is the basic platform as well as a place for early education for every child. The role of parents is very important in children's education. Parents who are able to position themselves as protectors, protectors, and educators of children will certainly be coherent in the hope that they will get good future generation candidates, because the nature of children is in need of love and attention from their parents. Will of Lukman al-Hakim in Q.S. Luqman verses 13-19 is a manifestation of the importance of children's education by parents in the family. Education in the family is not only limited to religious education, but also provides moral, personality and social education. Parents should be able to carry out holistic education to children in the family so that they can realize the goal of education, namely to make a complete person balanced between emotions, intellectuals, and spirituality Abstrak Artikel ini membahas tentang peran orang tua sebagai pendidik anak dalam rumah tangga. Para sarjana Muslim banyak menukil ayat-ayat qur’an dan hadis sebagai dasar petingnya pendidikan anak dalam keluarga. Keluarga sebagai instrumen terkecil dalam masyarakat dan sebagai peletak dasar sekaligus tempat pendidikan awal bagi setiap anak. Peran orang tua sangatlah pentingdalam pendidikan anak. Orang tua yang mampu memposisikan diri sebagai pelindung, pengayom, dan pendidik anak tentunya akan koheren dengan harapan agar mendapat calon generasi penerus yang baik, karena sifat dasar anak adalah membutuhkan kasih sayang dan rhatian dari orang tuanya. Wasiat Lukman al-Hakim dalam Q.S. Luqman ayat 13-19 merupakan manifestasi dari pentingnya pendidikan anak oleh orang tua dalam keluarga. Pendidikan dalam keluarga bukan hanya dibatasi dalam pendidikan agama saja, namun juga memberikan pendidikan akhlaq, kepribadian, dan sosial. Orang tua sepantasnya mampu melaksanakan pendidikan holistik kepada anak dalam keluarga sehingga mampu mewujudkan tujuan pendidikan yaitu menjadikan insan paripurna yang seimbang antara emosi, intelektual, dan spiritual.